ANALISIS FAKTOR SOSIAL DAN BUDAYA DALAM KECANDUAN PORNOGRAFI DI KALANGAN REMAJA KOTA DENPASAR - Alvin Lie; Aliffiati *; Ida Bagus Oka Wedasantara (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
The rapid development of technology has had a significant impact on adolescent behavior, including in the city of Denpasar. Pornography has become a part of everyday life that attracts the attention of teenagers and provides strong stimulation. Increased consumption of pornographic content can lead to pornography addiction, triggering negative impacts such as decreased morals, as well as various other problems. This research aims to reveal the influence of social and cultural factors on the behavior of teenagers who are addicted to pornography. The approach used to reveal the adolescent phenomenon is through a qualitative approach. The research results show that environmental factors, especially family environment, friendships and social media, have an important role in the development of pornography addiction among teenagers. Lack of attention, lack of communication between parents and children, and lack of supervision of children's use of devices can influence pornography consumption behavior. Apart from that, interactions with peers also have a big influence, where teenagers often seek validation from their peers and are influenced by group norms. So efforts need to be made to reduce or even prevent pornography addiction among teenagers in Denpasar City by taking self-control measures and learning in a good environment. Reflection carried out to prevent and anticipate pornography addiction among teenagers is an effort to avoid deviant actions.